Interactive textures for architecture and landscaping : digital elements and technologies - Wiberg, Mikael, 1974- (Newyork : Information Science Reference, 2011)
"This book addresses the phenomenon called "interactive architecture that challenges artists, architects, designers, theorists, and geographers to develop a language and designs toward the "use" of these environments"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Architecture and technology; Texture in architecture; Materials -- Technological innovations; Surfaces (Technology); Human-computer interaction; User interfaces (Computer systems)